Mathematical Concept Understanding of Middle School Students: An Experimental Study of the Discovery Learning Model - Ranggoli, Putri Wulandari; Achmad, Novianita; Kobandaha, Putri Ekawaty (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The role of conceptual understanding is essential because it enables students to more easily comprehend and learn mathematics. Therefore, this study focuses on the impact of the Discovery Learning model on the mathematical concept comprehension of students at a public middle school. The research employed an experimental method with a posttest-only control group design. The study's population included all eighth-grade students at public middle school 8 Gorontalo. The sample consisted of class VIII-5 as the experimental group, which implemented discovery learning, and class VIII-3 as the control group, which used a direct instruction learning model. Data was collected through an essay test administered as a post-test at the end of the study. Data analysis was performed descriptively and inferentially using a t-test. The results of the t-test indicated a t-calculated value of 3.506 and a t-table value of 1.6779, confirming that the t-calculated value is greater than the t-table value. Thus, it can be concluded that the Discovery Learning model has a significant influence on the mathematical concept comprehension of eighth-grade students at public middle school 8 in Gorontalo.